Defense against the black arts how hackers do what they do and how to protect against it - Varsalone, Jesse
As technology has developed, computer hackers have become increasingly sophisticated, mastering the ability to hack into even the most impenetrable systems. The best way to secure a system is to understand the tools hackers use and know how to circumvent them. Defense against the Black Arts: How Hackers Do What They Do and How to Protect against It provides hands-on instruction to a host of techniques used to hack into a variety of systems. Exposing hacker methodology with concrete examples, this book shows you how to outwit computer predators at their own game. Amon